2004
DOI: 10.1111/j.1523-1755.2004.00469.x
|View full text |Cite
|
Sign up to set email alerts
|

Blood oxygen level–dependent measurement of acute intra-renal ischemia

Abstract: This study shows that the BOLD technique can noninvasively detect change in intra-renal oxygenation during an acute reduction of RBF. This study provides a strong rationale for developing the BOLD method for the detection and evaluation of renal hypoxia induced by RAS, which may be potentially applicable in humans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
104
1
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 136 publications
(109 citation statements)
references
References 27 publications
2
104
1
2
Order By: Relevance
“…Renal oxygen consumption, V r O 2 ) (ml ⅐ min Ϫ1 ⅐ 100 g Ϫ1 ), was calculated as the product of RBF and the arterial-venous difference in O 2 content and normalized for renal weight (7,8). The arterial oxygen content (C a) was calculated by Ca ϭ (1.31 ⅐ Hb ⅐ SaO 2 ) ϩ (0.003 ⅐ PaO 2 ), and the renal venous content (C v) was calculated as Cv ϭ (1.31 ⅐ Hb ⅐ S rvO2)ϩ(0.003 ⅐ PrvO2), where Hb is hemoglobin concentration (mg/dl), SO 2 is O2 saturation (%) as determined by blood gas analysis in the artery ( a) or vein (rv), and PO2 is the arterial (a) or renal vein ( rv) oxygen tension (mmHg).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Renal oxygen consumption, V r O 2 ) (ml ⅐ min Ϫ1 ⅐ 100 g Ϫ1 ), was calculated as the product of RBF and the arterial-venous difference in O 2 content and normalized for renal weight (7,8). The arterial oxygen content (C a) was calculated by Ca ϭ (1.31 ⅐ Hb ⅐ SaO 2 ) ϩ (0.003 ⅐ PaO 2 ), and the renal venous content (C v) was calculated as Cv ϭ (1.31 ⅐ Hb ⅐ S rvO2)ϩ(0.003 ⅐ PrvO2), where Hb is hemoglobin concentration (mg/dl), SO 2 is O2 saturation (%) as determined by blood gas analysis in the artery ( a) or vein (rv), and PO2 is the arterial (a) or renal vein ( rv) oxygen tension (mmHg).…”
Section: Methodsmentioning
confidence: 99%
“…Nevertheless, prior work in our laboratory (7) suggests that renal tissue oxygenation (P t O 2 ) may be impaired during acute renal arterial stenosis. Therefore, the present study was designed to test the hypothesis that despite proportional changes in whole kidney O 2 delivery and consumption, acute progressive renal arterial stenosis (RAS) leads to decreases in regional renal tissue oxygenation.…”
mentioning
confidence: 90%
“…In a model of acute renal arterial occlusion, BOLD revealed that increases in R 2 * paralleled the level of occlusion and reduction of renal blood flow (32). Indeed, patient with significant (33), but not moderate (34), renal artery stenosis show decreased renal oxygenation compared with essential hypertension.…”
Section: Blood Oxygen Level-dependent Mrimentioning
confidence: 96%
“…Blood oxygenation level-dependent (BOLD) magnetic resonance imaging (MRI) has been shown to be very useful in monitoring intrarenal oxygenation. [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] A major advantage of the noninvasive BOLD MRI is the ability to perform similar measurement in humans.…”
mentioning
confidence: 99%